Acute Respiratory Distress Syndrome Associated With Clopidogrel in a Young Male Patient - Roses, Stephanie M.; Christianson, Thomas; Dombrowski, Keith (Frontiers in Medicine, 2019)
Background: Clopidogrel is a commonly prescribed antiplatelet drug in patients with stents and histories of arterial vascular disease. It generally has a favorable side effect profile with increasing bleeding risk as the main concern as an adverse event. Case Presentation: A 19-year-old previously healthy male presented to the neurological intensive care unit with a subarachnoid hemorrhage requiring a flow diverting stent to secure the aneurysm. The patient was stable for 2 weeks and had no changes to management or medication within 48 h of antiplatelet therapy. Within hours of first-time dosing of clopidogrel, the patient experienced a syncopal episode and dyspnea. He was difficult to arouse and using accessory muscles to breath with an otherwise benign exam. He was hypoxic with bibasilar crackles requiring bilevel positive airway pressure (BiPap). Imaging showed bilateral pulmonary edema and he was diagnosed with moderate acute respiratory distress syndrome (ARDS). Infectious, cardiogenic, and contrast-induced ARDS were ruled out. Upon cessation of clopidogrel, his pulmonary function and mental status improved. Conclusions: This is the first reported case of a young and immunocompetent patient's severe pulmonary edema leading to acute respiratory distress syndrome in association with first- time dosing of clopidogrel.